PSIV-12 Molecular distribution and localization of bitter receptor (T2R1) in different tissues including intestinal segments in weaned piglets. (7th December 2018) - Yang, C; Li, W; Schindell, B; Ni, L; Liu, S; Gong, J; Yang, C
Abstract: Bitter receptor (taste 2 receptor member 1, T2R1) belongs to a class of G-protein-coupled receptors (GPCR) and recognizes bitter compounds in animal diets. However, the molecular distribution and localization of pig T2R1 (pT2R1) in different tissues and along the longitudinal axis of the intestine in pigs are still unknown. In the present study, we investigated the molecular distribution and localization of pT2R1 in different tissues including intestinal segments of weaning piglet. Six male pigs ([Yorkshine-Landrace] × Duroc, weaned at 21 ± 2 d) at the age of 28 d were anesthetized by an intramuscular injection of ketamine:xylazine and euthanized by intravenous injection of sodium pentobarbital. Different tissues including intestinal segments were collected. The pT2R1 mRNA abundance and protein localization were measured by real-time PCR and immunohistochemistry, respectively. The predicted full-length pT2R1 mRNA sequence has 63.53%, 71.88% and 49.26% homology with that of mouse, human and chicken, respectively. The pT2R1 protein sequence has 48.82%, 53.51% and 28.86% homology with that of mouse, human and chicken, respectively. Phylogenetic analysis indicated that pig T2R1 were relatively far away with chicken's T2R1. The pT2R1 has seven transmembrane (TM) helixes, three extracellular loops and three intracellular loops. The mRNA and protein of pT2R1 were detected in the tongue, kidney, lung, liver, stomach, duodenum, jejunum, ileum and colon in weaned piglets. The pT2R1 mRNA was much higher in the stomach when compared with other tissues ( P < 0.05). The duodenum and ileum had higher pT2R1 mRNA abundance than the kidney, lung, tongue, jejunum and colon ( P < 0.05). These results demonstrate that bitter receptor pT2R1 is expressed both in taste and non-taste tissues in weaning piglets. The functional characterization of pT2R1 gene and its ligands need to be further investigated.